The Relationship of Physical Activity, Energy, and Protein Intake with Nutritional Status in Adolescents at Junior High School - Taufik Taufik; Astri Ayu Novaria; Riana Pangestu Utami; Wiryanto Wiryanto (Media Publikasi Cendekia Indonesia, 2024)
Indonesia is still in a nutritional emergency. Undernutrition or overnutrition is a health problem that is often found in adolescence. Nutritional problems that occur are influenced by an imbalance between physical activity and macronutrient intake in adolescents. This study aims to determine the relationship between physical activity, energy intake, and protein intake with nutritional status in adolescent girls. Observational study with a cross-sectional approach conducted in July – August 2023 at Junior High School 2 Long Bagun, Mahakam Ulu Regency, East Kalimantan. A total of 42 adolescents were included as samples based on purposive sampling by setting inclusion and exclusion criteria. Physical activity variables were measured in the International Physical Activity Questioner (IPAQ) while energy and protein intake were obtained through a 24-hour food recall form. The BMI / U formula measures nutritional status-data analysis using the Spearman Rank correlation test. Our findings show the majority of adolescents with moderate physical activity (76.2%), adequate energy intake (66.7%), and adequate protein intake (66.6%). The results of the relationship analysis showed physical activity (p = 0.001, r = 0.512), energy intake (p = 0.001, r = 0.503), protein intake (p = 0.002, r = 0.459) with the nutritional status of adolescents at Junior High School 2 Long Bagun. There is a significant relationship between physical activity, energy intake, and protein intake with the nutritional status of adolescents at Junior High School 2 Long Bagun. These findings are empirical evidence for the formation of better adolescent health programs